2015
DOI: 10.1186/s12888-015-0450-9
|View full text |Cite
|
Sign up to set email alerts
|

Olanzapine long-acting injection: a review of first experiences of post-injection delirium/sedation syndrome in routine clinical practice

Abstract: BackgroundOlanzapine long-acting injection (LAI) for the treatment of schizophrenia was associated with a cluster of symptoms termed post-injection delirium/sedation syndrome (PDSS) in a small percentage (~2%) of patients during clinical trials. The objective of this analysis was to evaluate the rate and clinical characteristics of PDSS since olanzapine LAI entered commercial use.MethodsCases of PDSS were identified from all reported adverse events during worldwide commercial use of olanzapine LAI through to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 13 publications
7
31
0
Order By: Relevance
“…route of administration. In particular, post-injection delirium/sedation syndrome, characterized by sedation (including coma) and/or delirium has been reported in approximately <0.1% of injections [133][134] Patients with cardiac impairment should be carefully monitored for the increasing risk of orthostatic hypotension. Although olanzapine is not recommended in children and adolescents, preliminary clinical data suggest its relative safety and efficacy for the treatment of behavioral disturbances.…”
Section: Adverse Effectsmentioning
confidence: 99%
“…route of administration. In particular, post-injection delirium/sedation syndrome, characterized by sedation (including coma) and/or delirium has been reported in approximately <0.1% of injections [133][134] Patients with cardiac impairment should be carefully monitored for the increasing risk of orthostatic hypotension. Although olanzapine is not recommended in children and adolescents, preliminary clinical data suggest its relative safety and efficacy for the treatment of behavioral disturbances.…”
Section: Adverse Effectsmentioning
confidence: 99%
“…Cases of patients with PDSS have been reported in the literature. Most of them needed only supportive medical care and all recovered in 1.5–72 hours after injection 4 5…”
Section: Discussionmentioning
confidence: 99%
“…5 The occurrence rate seems to be similar in real-world clinical practice according to ongoing studies. 3 Current data regarding occurrence, development, manifestation, treatment, and outcome of PDSS are still limited. In a review article published in CNS Drugs 2015, the authors claim that only one case of PDSS has been mentioned in connection with OLAI since the last clinical trial ended in August 2008, 11 whereas a recent study based on postmarketing safety studies and spontaneous reports found a total of 338 PDSS events between March 1, 2009, and March 1, 2014.…”
Section: Discussionmentioning
confidence: 99%
“…1 Olanzapine long-acting injectable, or OLAI, has been associated with the potentially serious adverse event termed postinjection delirium/sedation syndrome (PDSS), caused by high serum concentrations of olanzapine resulting from unintended intravascular injection of OLAI. [2][3][4] Signs and symptoms of PDSS are consistent with olanzapine overdose, including sedation (ranging from mild in severity to coma) and/or delirium (including confusion, disorientation, agitation, anxiety, and other cognitive impairment). Further symptoms noted include extrapyramidal symptoms, dysarthria, ataxia, aggression, dizziness, weakness, hypertension, and seizure.…”
mentioning
confidence: 99%
See 1 more Smart Citation